A sliding mode observer design for single phase photovoltaic grid integration. (2018) - Sahoo, Pradipta Kumar; Ray, Pravat Kumar; Das, Pranati
In this paper, solar array current is estimated and observed with a sliding mode observer instead of having a sensor, the observer is based on sliding-mode control and is constructed from the dynamic equations of the considered system vis. a single phase grid connected photovoltaic system that has a photovoltaic module and a single-phase H-bridge inverter. The solar array current is observed by the known values or measured values of the array voltage and inductor current. The current estimation is governed by the sliding mode observer gain, with decrease in the value of the gain, chattering problems become reduce. Observer gain has been varied from 100% of designed value to 6.25% of its value. A compromise has been made between estimation accuracy and chattering, to get an effective result at 12.5% of the designed value of observer gain. The estimated value almost follows the original current and hence, is used to track the MPP rapidly. Methodology of grid integration of distributed photovoltaic systems is explored and simulated using MATLAB/Simulink. The simulation results prove the effectiveness of the proposed method for efficient grid integration.